Genetic similarities and phylogenetic analysis of Muntjac (Muntiacus spp.) by comparing the nucleotide sequence of 16S rRNA and cytochrome B genome - Khan,B. M. (2023)
Abstract This study aimed to identify the phylogenetic similarities among the muntjac (Muntiacus spp.). The phylogenetic similarities among seven major muntjac species were studied by comparing the nucleotide sequence of 16s rRNA and cytochrome b genome. Nucleotide sequences, retrieved from NCBI databases were aligned by using DNASTAR software. A phylogenetic tree was created for the selected species of muntjac by using the maximum likelihood method on MEGA7 software. The results of nucleotide sequences (16s rRNA) showed phylogenetic similarities between, the M. truongsonensis and M. rooseveltorum had the highest (99.2%) while the lowest similarities (96.8%) found between M. crinifrons and M. putaoensi. While the results of nucleotide sequences (Cty b) showed the highest similarity (100%) between M. muntjak and M. truongsonensis and the lowest s (91.5%) among M. putaoensis and M. crinifrons. The phylogenetic tree of muntjac species (16s rRNA gene) shows the main two clusters, the one including M. putaoensis, M. truongsonensis, M. rooseveltorum, and M. muntjak, and the second one including M. crinifrons and M. vuquangensis. The M. reevesi exists separately in the phylogenetic tree. The phylogenetic tree of muntjac species using cytochrome b genes shows that the M. muntjak and M. truongsonensis are clustered in the same group.